2011
DOI: 10.1103/physrevlett.106.216601
|View full text |Cite
|
Sign up to set email alerts
|

Spin Pumping by Parametrically Excited Exchange Magnons

Abstract: We experimentally show that exchange magnons can be detected by using a combination of spin pumping and the inverse spin-Hall effect proving its wavelength integrating capability down to the submicrometer scale. The magnons were injected in a ferrite yttrium iron garnet film by parametric pumping and the inverse spin-Hall effect voltage was detected in an attached Pt layer. The role of the density, wavelength, and spatial localization of the magnons for the spin pumping efficiency is revealed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
242
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(256 citation statements)
references
References 18 publications
12
242
1
1
Order By: Relevance
“…As such, it is the theoretical maximum. The other parameter that will have the largest impact on the numerical solution to eqns (3) and (4) …”
Section: Appendix D: Effect Of Spin Sinking and The Upper Bound Of Mamentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it is the theoretical maximum. The other parameter that will have the largest impact on the numerical solution to eqns (3) and (4) …”
Section: Appendix D: Effect Of Spin Sinking and The Upper Bound Of Mamentioning
confidence: 99%
“…In magnetically ordered insulators, spin currents are carried by magnons. These spin currents are typically generated via the spin Hall effect [2] or through spin pumping, in which a microwave magnetic field excites spin-waves of approximately 10 GHz [3] . Such microwave frequency spin-waves have been proposed for use in logic devices with low power consumption [4], and recently an all-magnon based transistor was demonstrated [5].…”
Section: Introductionmentioning
confidence: 99%
“…"Backward" waves have a frequency dispersion with a negative group velocity for some wavelengths. While these spin waves have been studied in great detail over the last decades, the effect of an adjacent normal metal on these waves has only recently been investigated.Experimentally, it has been observed that spinpumping differs for FVMSWs, BVMSWs and MSSWs and that it depends on the spin-wave wavelength [6,8,9,[12][13][14]. Recent experiments [8] have demonstrated that the magnetization dissipation is larger for surface spin waves in which the excitation amplitude is localized at the magnetic insulator-normal metal interface.…”
mentioning
confidence: 99%
“…Experimentally, it has been observed that spinpumping differs for FVMSWs, BVMSWs and MSSWs and that it depends on the spin-wave wavelength [6,8,9,[12][13][14]. Recent experiments [8] have demonstrated that the magnetization dissipation is larger for surface spin waves in which the excitation amplitude is localized at the magnetic insulator-normal metal interface.…”
mentioning
confidence: 99%
See 1 more Smart Citation